Budaya berfikir kritis: Kajian di era pemerintahan Khalifah ‘Umar bin ‘Abd-‘Al-Aziz (99-101H) / Norafifah Ab. Hamid - Norafifah , Ab. Hamid (2010)
The citical thinking culture is not an accustomed method of thinking in fact Islamic teachings do stress in critical thinking aspect. Al-Quran and Al-Sunnah also emphasize on critical thinking. Moreover, the critical thinking culture has been practiced during the Prophet Muhammad s.a.w’s, Khulafa’ al-Rasyidin’s and tabi’in’s era. This research sift through the instilation of critical thinking culture in the Caliph ‘Umar bin Abd al-‘Aziz’s administration era. Generally this research carried out to examine how far Caliph ‘Umar bin ‘Abd al-‘Aziz has been trained to practice this culture before he mastered it. Besides, this research also examine how far this critical thinking may contribute towards creating peaceful and harmonious environment in the Muslim’s community in his era of administration. The outcome of this research shows that Caliph ‘Umar has succeeded in instiling the critical thinking culture during the era that he has leads. The main elements of the critical thinking are analytical, objectivity and evaluation has been emphasized by Caliph ‘Umar. Thus, it can be concluded that Caliph ‘Umar has succeeded in creating a fair justice, peaceful and harmonious administration from the effect of the instilition of critical thinking culture.